2023
DOI: 10.5009/gnl220342
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of ARID1A Expression Patterns Varies with Molecular Subtype in Advanced Gastric Cancer

Abstract: Background/Aims: AT-rich interactive domain 1A (ARID1A) is frequently mutated in gastric cancer (GC), especially Epstein-Barr virus (EBV)-associated and microsatellite instability high GC. The loss of ARID1A expression has been reported as a poor prognostic marker in GC. However, the relationships between ARID1A alteration and EBV-associated and microsatellite instability high GC, which are known to have a favorable prognosis, has hampered proper evaluation of the prognostic significance of ARID1A expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…While Zhou et al have reported lower ARID1A protein expression levels in GCs compared to normal gastric tissue, recent studies suggest that complete or partial loss of ARID1A expression is associated with both reduced progression-free survival (PFS) and overall survival (OS) in patients with GC [ 15 , 20 , 22 , 29 , 36 , 37 , 38 , 39 ]. In this respect, Wang et al performed an immunohistochemical and molecular study of 272 primary GCs, where ARID1A protein deletion emerged as an independent risk factor of poor prognosis [ 29 ]. More specifically, a correlation between ARID1A deletion and critical clinico-pathological parameters including tumor differentiation, lymph node metastasis, and tumor size has also been demonstrated [ 36 ].…”
Section: Clinical and Prognostic Significance Of Arid1a ...mentioning
confidence: 99%
See 2 more Smart Citations
“…While Zhou et al have reported lower ARID1A protein expression levels in GCs compared to normal gastric tissue, recent studies suggest that complete or partial loss of ARID1A expression is associated with both reduced progression-free survival (PFS) and overall survival (OS) in patients with GC [ 15 , 20 , 22 , 29 , 36 , 37 , 38 , 39 ]. In this respect, Wang et al performed an immunohistochemical and molecular study of 272 primary GCs, where ARID1A protein deletion emerged as an independent risk factor of poor prognosis [ 29 ]. More specifically, a correlation between ARID1A deletion and critical clinico-pathological parameters including tumor differentiation, lymph node metastasis, and tumor size has also been demonstrated [ 36 ].…”
Section: Clinical and Prognostic Significance Of Arid1a ...mentioning
confidence: 99%
“…More specifically, a correlation between ARID1A deletion and critical clinico-pathological parameters including tumor differentiation, lymph node metastasis, and tumor size has also been demonstrated [ 36 ]. However, other studies challenge the notion that an absence of ARID1A protein expression is a marker of poor prognosis [ 29 , 30 , 39 ]. For instance, Ibarrola–Villava and co-workers have reported that patients with absent ARID1A expression had a significantly higher OS compared to those with positive expression profiles [ 30 ].…”
Section: Clinical and Prognostic Significance Of Arid1a ...mentioning
confidence: 99%
See 1 more Smart Citation